2022
DOI: 10.1093/eurpub/ckac019
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial workplace factors and alcohol-related morbidity: a prospective study of 3 million Swedish workers

Abstract: Background Psychosocial workplace factors may be associated with alcohol-related morbidity, but previous studies have had limited opportunities to take non-occupational explanatory factors into account. The aim of this study is to investigate associations between job control, job demands and their combination (job strain) and diagnosed alcohol-related morbidity while accounting for several potentially confounding factors measured across the life-course, including education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…Details of the construction and its validity are described in a previous publication (Fredlund et al 2000 ), but external validation has not been possible. However, results in several recent studies using this JEM (Almroth et al 2021 ; Almroth et al 2022a , b ) were consistent with similar studies from other countries.…”
Section: Methodssupporting
confidence: 88%
“…Details of the construction and its validity are described in a previous publication (Fredlund et al 2000 ), but external validation has not been possible. However, results in several recent studies using this JEM (Almroth et al 2021 ; Almroth et al 2022a , b ) were consistent with similar studies from other countries.…”
Section: Methodssupporting
confidence: 88%
“…One explanation could be that women in these occupations may have greater access to lethal means. However, in previous studies of the same population, we have also found that this group of women has an increased risk of both depression and alcohol-related morbidity,11 12 indicating that there may be unique risk factors of this specific group. Additionally, the medium-low control group tended to be more disadvantaged from baseline regarding childhood factors, mental health, education and sick leave.…”
Section: Discussionmentioning
confidence: 60%
“…Beyond such a specific circumstance, one of the most common ways of quantifying work-related psychosocial stress is the demand-control model 8. Some studies have found that the combination of low job control and high job demands (job strain) is related to adverse psychological outcomes,5 9 but job control tends to be the more consistent predictor of alcohol related morbidity,10 11 depression12 13 and suicide ideation14 in many studies. Some experts even argue that it may be job control which is driving observed associations between job strain and psychiatric outcomes 15 16…”
Section: Introductionmentioning
confidence: 99%
“…In der kürzlich publizierten prospektiven Megastudie von Almroth u. Mitarb. 2022 mit 3 Millionen eingeschlossenen schwedischen Arbeitern verlor der Zusammenhang mit alkoholbedingter Morbidität nach Kontrolle weiterer Einflussfaktoren (insbesondere die Sozialschicht) an Signifikanz [8]. Zum Einfluss von Arbeitsstress auf Nikotinkonsum legte das IPD-Work-Consortium eine große epidemiologische Studie mit 166 130 Teilnehmern vor und ermittelte einen moderaten Effekt (OR 1,11; 95%-KI 1,03-1,18) [9].…”
Section: Gesundheitsschädigende Kompensationsversuche Von Arbeitsstressunclassified